A simple and green methodology to assemble poly(4-vinylpyridine) and a sulfonated azo-dye for obtaining stable polymeric nanoparticles. (5th December 2018) - Catalán-Toledo, José; Nenen, Ariel; Vallejos, Gabriel A.; Oyarzun-Ampuero, Felipe; Shibue, Toshimichi; Nishide, Hiroyuki; Moreno-Villoslada, Ignacio
Abstract: A new green and simple method of synthesis of polymeric nanoparticles comprising a pH-responsive polymer and a sulfonated dye, without needing the use of any organic solvent or cross-linker, is shown. It is based on the complexation between weak basic aromatic polyelectrolytes and a strong acidic dye by means of aromatic-aromatic interactions in water at acidic pH, and subsequent fast pH change, which triggers a controlled collapse of the system in the form of nanoparticles. Poly(4-vinylpyridine) and the tetrasulfonated azo dye 4, 4'-((1E, 1′ E )-(3, 3′-dimethyl-[1, 1′ biphenyl]-4, 4′diyl)bis(diazen-2, 1-diyl))bis(3-hidroxynaphtalen-2, 7-disulfonate) form complexes at pH 3–5, undergoing short-range aromatic-aromatic interactions, as seen by 1 H NMR. Subsequent and fast pH adjustment to 9–10 leads to the system collapse with faster kinetics than those for the hydration and release of the hydrophilic negatively charged dye, so that polymeric nanoparticles are formed that include the dye, which acts as stabilizer. The monomodal distributed nanoparticles showed 50–200 nm of hydrodynamic diameter, with PDI ranging between 0.1 and 0.4, and zeta potential values in the range −40 to −60 mV, resulting stable for at least 14 days. The synthesized nanoparticles have been included in calcium alginate beads, showing colorimetric sensitivity to pH changes in water. We envisage that our findings could be also applied in other hydrophilic-aromatic polymers to create stable and functional materials by using this simple and green methodology. Graphical abstract: Highlights: Poly(4-vinylpyridine) forms nanoaggregates with a sulfonated dye at acid pH. The molecules bind by aromatic-aromatic interactions as seen by 1 H NMR. Upon fast pH adjustment over pH 9 polymeric nanoparticles are formed. The nanoparticles show colorimetric response included in calcium alginate beads.